2017
DOI: 10.1007/s40120-017-0072-x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Biomarkers for Neurodegenerative Disease: Will They Swing Us Across the Valley?

Abstract: Measures of the severity of cognitive impairment or parkinsonism are the usual endpoints in clinical trials for Alzheimer’s disease (AD) and Parkinson’s disease (PD), but are critically hampered by their lack of disease sensitivity and specificity. Due to the high failure rate of clinical trials, the rate of regulatory approval for efficacious new drugs has stagnated in the past few decades, with the gap between basic science discovery and clinical application metaphorically termed the “Valley of Death”. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 81 publications
0
26
0
1
Order By: Relevance
“…While the core amyloid-β (Aβ) and tau biomarkers of AD [ 16 , 17 ] are highly associated with the presence of signature plaque and tangle pathological hallmarks of AD in the brain [ 16 ], they do not assess other fundamental biochemical aspects of the disease, such as non-amyloid and non-tau neurodegeneration or metabolic, immune, and neurovascular dysfunction [ 18 21 ]. A panel of robust biomarkers that directly reflect these concomitant pathophysiologies may prove a better indicator of disease diagnosis [ 22 , 23 ], subtypes, staging, and activity, as well as treatment-specific target engagement.…”
Section: Introductionmentioning
confidence: 99%
“…While the core amyloid-β (Aβ) and tau biomarkers of AD [ 16 , 17 ] are highly associated with the presence of signature plaque and tangle pathological hallmarks of AD in the brain [ 16 ], they do not assess other fundamental biochemical aspects of the disease, such as non-amyloid and non-tau neurodegeneration or metabolic, immune, and neurovascular dysfunction [ 18 21 ]. A panel of robust biomarkers that directly reflect these concomitant pathophysiologies may prove a better indicator of disease diagnosis [ 22 , 23 ], subtypes, staging, and activity, as well as treatment-specific target engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Fleming and Powers provide a precise definition of what a surrogate endpoint is and also give several examples. In recent literature, the adoption of biomarkers as surrogate endpoints has been argued within neurodegenerative diseases and cancer trials, and it has even been suggested that these techniques be applied to other clinical fields . Unfortunately, we found no data on success rates in trials in which surrogate endpoints have been used.…”
Section: Strategies To Reduce Phase III Failures In Principlementioning
confidence: 74%
“…It is presumed that exosomes play an important role by facilitating the interneuronal transport of the proteins [114]. As well, there is a critical need in finding accessible biomarkers that can diagnose a neurodegenerative disease in the asymptomatic stage [115]. Dosing certain free proteins in biofluids can be an option, but several problems are experienced because of their low concentrations [115].…”
Section: Extracellular Vesicles' Perspective Use In Brain Pathologymentioning
confidence: 99%
“…As well, there is a critical need in finding accessible biomarkers that can diagnose a neurodegenerative disease in the asymptomatic stage [115]. Dosing certain free proteins in biofluids can be an option, but several problems are experienced because of their low concentrations [115]. Therefore, a new approach is being attempted consisting in finding the proteins encapsulated in extracellular vesicles [116].…”
Section: Extracellular Vesicles' Perspective Use In Brain Pathologymentioning
confidence: 99%